2008
DOI: 10.1007/s10461-008-9380-6
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Differences in HIV Sexual Transmission among Latino and Black Men who have Sex with Men: The Brothers y Hermanos Study

Abstract: HIV sexual transmission risk behaviors were examined among 1,065 Latino and 1,140 black men who have sex with men (MSM). Participants completed a computer-administered questionnaire and were tested for HIV infection. Of men who reported that their last HIV test was negative or that they had never been tested or did not get the result of their last test, 17% of black and 5% of Latino MSM tested HIV-positive in our study. In both ethnic groups, the three-month prevalence of unprotected anal intercourse (UAI) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
50
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 26 publications
2
50
0
Order By: Relevance
“…As other authors have found, 9,14,16,17,[36][37][38] patterns of MSM disclosure were differential with respect to race/ethnicity, with black MSM being less likely to disclose MSM behavior to family members, non-gay-identified friends, and health care providers. Differences in disclosure of MSM behavior even after adjustment for age may represent differing cultural norms between groups.…”
Section: Discussionmentioning
confidence: 57%
“…As other authors have found, 9,14,16,17,[36][37][38] patterns of MSM disclosure were differential with respect to race/ethnicity, with black MSM being less likely to disclose MSM behavior to family members, non-gay-identified friends, and health care providers. Differences in disclosure of MSM behavior even after adjustment for age may represent differing cultural norms between groups.…”
Section: Discussionmentioning
confidence: 57%
“…The failure to generate a representative sample has been found in some prior studies of MSM, 21,22,34 in which the sample overrepresented poor and HIV-positive MSM. In one case, the overrepresentation of HIV-positive MSM was attributed to errors in the operationalization of eligibility criteria and a large network from an HIV/AIDS service organization; 34 the overrepresentation of poor individuals was attributed to motivation due to the incentive structure.…”
Section: Discussionmentioning
confidence: 98%
“…In one case, the overrepresentation of HIV-positive MSM was attributed to errors in the operationalization of eligibility criteria and a large network from an HIV/AIDS service organization; 34 the overrepresentation of poor individuals was attributed to motivation due to the incentive structure. 21,22,34 It is possible that, although chains were sometimes quite long in these studies, they were not long enough to offset a high degree of segmentation by race/ethnicity, poverty, and HIV status.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of point-of-care rapid HIV testing technologies has made HIV testing more accessible, with test results available in as few as 20 minutes. Several studies have shown that persons who are aware of their HIV infection reduce risky sexual behaviors and are more likely to prevent HIV transmission (Marks, Crepaz, Senterfitt, & Janssen, 2005;Marks et al, 2009;Weinhardt, Carey, Johnson, & Bickham, 1999).…”
mentioning
confidence: 99%